Utilization of empon-empon stem waste in the creation of eco-friendly homeware products - Sumarno Sumarno; Raden Ersnathan Budi Prasetyo; Agung Cahyana; Catur Sugiarto (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2024)
Empon-empon stems, considered agricultural waste, present an untapped resource for crafting natural fiber products. While materials like banana stems, water hyacinth, and jute are commonly used for this purpose, empon-empon stems offer a novel alternative. This study explores the potential of empon-empon stems in creating ropes and other homeware products, aiming to not only reduce agricultural waste but also to provide additional income streams for farmers. The research methodology involves a comprehensive process of harvesting, separating, drying, and twisting empon-empon stems into rope. Additionally, a design-driven material (DDM) approach is employed to convert the rope into various products such as baskets, planter stands, and trays. The DDM approach includes analyzing material characteristics, visual exploration, creating shop drawings, and producing prototypes. The results demonstrate that empon-empon rope products are not only functional and aesthetically pleasing but also carry a unique aroma, adding to their appeal. These products have the potential to address the shortage of natural fibers in the craft industry and can serve as an alternative material for interior design applications. In conclusion, this research highlights the feasibility of utilizing empon-empon stems as a sustainable material for crafting innovative homeware products. By transforming agricultural waste into valuable goods, this approach contributes to both environmental sustainability and economic development in rural areas.